Introduction to euroCRIS and some relevant developments going on in the CRIS domain - Simons, Ed (2018)
An international not-for-profit association of experts and users of research information and research information systems (CRIS), legally based in The Netherlands. Main activities: Development and governance of CERIF, a standard data model and exchange format for research information, and the promotion of its use. Promotion of community building and cooperation within he esearch Information Domain. To fulfill this unction, euroCRIS regularly organises international events: Membership Meetings and Conferences, as well as concluding (strategic) partnerships with other stakeholder organisations in the RI domain. Upcoming events: strategic Membership Meeting, Warsaw, 26-28 November 2018